Evolutionary Mapping of the Research Landscape and Bibliometric Analysis of Blockchain Technology in Finance - Ayodele, Olamide Emmanuel; Oluwabiyi, Opeoluwa Kofoworola; Ajibade, Temiloluwa Iyanuoluwa; Ajibade, Samuel-Soma M.; Jasser, Muhammed Basheer; ALDharhani, Ghassan Saleh; Al-Hadi, Ismail Ahmed Al-Qasem (International Journal of Economics and Financial Issues, 2025)
The study examines research on Blockchain technology in the global finance using trends analysis, bibliometric analysis, and literature review using the Elsevier Scopus database from 2016-2023. The findings showed that (Blockchain in Financial Management) BCFin research has generated 185 publications comprising 53.5% articles, 45.4% conference proceedings and 1.1% reviews. The subject area analysis revealed three major publications, groupings spanning Computer Science, Engineering, and Decision Sciences. In contrast, the source titles revealed ACM International Conference Proceeding Series, Sustainability Switzerland, and E3S Web of Conferences as the top mediums of publications for BCF in researchers. Stakeholders analysis showed that the top researchers and affiliations for BCFin are Jon M. Truby and Qatar University (Qatar), with 4 and % publications, respectively. The most productive nation on the topic is China, which is largely ascribed to active funding agencies such as the National Natural Science Foundation (NNSF) of China, which has funded 18 publications. Keywords Co-occurrence Analysis revealed that the top three keywords on BCFin are Blockchain, Finance, and Supply Chain Finance. Cluster analysis revealed three (3) clusters comprising 4-8 keywords, 132 links, and a TLS of 866. Based on the keywords, these clusters could be broadly categorised as the following terms: Integrated Business Solutions (Cluster 1), Digital Commerce Infrastructure (Cluster 2), and Decentralized Financial Network (Cluster 3). The findings indicate that BCFin is an active, multidisciplinary, and impactful research area. BCFin has transformed the global financial industry by overcoming trust issues, enhancing transaction security, and improving communication effectiveness, but it still faces challenges like interoperability, system integration, and sustainability.